SINTESIS ANTIGEN AFLATOKSIN M1-OVA ALBUMIN (Ova) SEBAGAI PEREAKSI AGAR GEL PRECIPITATION TEST (AGPT) - Fusvita, Angriani (Jurnal BioWallacea, 2015)
Synthesis aflatoksin M1 -Ova albumin (Ova) antigen used as Agar Gel Precipitation Test(AGPT) reagent. The AFM1-Ova antigen was synthesized by reacting AFM1 standard andOva albumin using carboxymethoxylamine hemihydrochloride (CMO) as intermediatereactions. The component of Reagent were AFM1-Ova antigen and antibody G (Ig G/serum)used for AGPT. The result of AFM1-Ova Antigen synthesis were 3,45 mg/ml. AGPT resultshowed bond precipitation reaction beetween specific antibody with AFM1-Ova antigen.Therefore synthesis of AFM1-Ova antigen can be used to serology reagent test as AGPT.Keywords : Aflatoxin, Ova albumin, Aspergillus flavus, Antigen